165k views
3 votes
Use the rule for order of operations to simplify the expression as much as possible:5 [4 + 2 ( 3 ⋅ 5 − 8 )] =

User NetAction
by
4.6k points

1 Answer

5 votes

Answer: 90

Step-by-step explanation:

The order of operations is termed PEMDAS

where

P = parentheses

E = exponent

M = multiplication

D = division

A = addition

S = subtraction

By simplifying the parentheses first, we have

3 * 5 = 15

15 - 8 = 7

The expression becomes

5[4 + 2(7)] =

2 * 7 = 14

4 + 14 = 18

The expression becomes

5[18]

= 90

User Nick Peachey
by
5.3k points